Opportunities of the Law “On State Civil Service” (Zien Journal of Social Sciences and Humanities, 2023)
This article explains the essence of the adopted Law "On the State Civil Service" using various examples. Based on the comparative-critical method, the norms defined in the law were compared with the laws of foreign countries. Prove that the purpose of the law is to regulate relations in the field of civil service.